Ultrasound examination of the lower limbs 2nd edition, revised and updated - Musil, Dalibor; al. et (Grada, 2024)
​This monograph focuses on the clinical use of ultrasound in phlebology. The core of the book is a description of the principal nosological units in phlebology and methods for their sonographic diagnosis. The second edition is available in English language and you can buy it in digital version (epub or pdf) only.
Keywords: Kardiologie, angiologie